Development of the Method of Formation of the Architecture of the Innovation Program in the System "University–State–Business" - Piterska, Varvara; Rudenko, Sergey; Shakhov, Anatoliy (International Journal of Engineering and Technology, 2018)
We investigated the mechanisms of increase of efficiency of innovative activity on the basis of methodology of management of projects and programs of sustainable development on the basis of the GPM Global P5 standard as well as the triple helix model "University–State–Business". This method takes into account the current trends of program and project management of innovation. The mechanism of target distribution for universities 1.0, 2.0, 3.0, 4.0 is investigated. Suggested model of the innovation program management is based on the model of the triple helix interaction and allows to take into account the interests of all groups of stakeholders. The mechanism of formation of the mission of the innovation program, which allows to determine the strategic goals of the innovation program participants, namely – the competitiveness of the University for higher education institutions, the quality of life of the population for the state and the profit for business. The method of formation of the architecture of the innovation program in the system "University–State–Business" has been developed with the integration of the interests of all participants of the program. The method of creating an office of management of the innovation program is proposed taking into account the model of the architecture of the innovation program.